2018
DOI: 10.1007/s11356-018-2401-8
|View full text |Cite
|
Sign up to set email alerts
|

Is skewed income distribution good for environmental quality? A comparative analysis among selected BRICS countries

Abstract: A large number of studies have examined the linkage between income inequality and environmental quality at the individual country levels. This study attempts to examine the linkage between the two factors for the individual BRICS economies from a comparative perspective, which is scarce in the literature. It examines the selected countries (Brazil, India, China and South Africa) by endogenising the patterns of primary energy consumption (coal use and petroleum use), total primary energy consumption, economic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 74 publications
6
18
0
Order By: Relevance
“…In GMM, the GDP per capita is positive and significant, indicating that an increase in the growth rate of countries will lead to an increase in the number of carbon emissions in the long run. This evidence is consistent with the studies of (Jayanthakumaran et al 2012;Wu et al 2015;Mahalik et al 2018). This study is the first empirical analysis of most emerging countries taking as pollution, energy consumption, OFDI in a single lens.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 93%
“…In GMM, the GDP per capita is positive and significant, indicating that an increase in the growth rate of countries will lead to an increase in the number of carbon emissions in the long run. This evidence is consistent with the studies of (Jayanthakumaran et al 2012;Wu et al 2015;Mahalik et al 2018). This study is the first empirical analysis of most emerging countries taking as pollution, energy consumption, OFDI in a single lens.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 93%
“…In GMM, the GDP per capita is positive and significant, indicating that an increase in the growth rate of countries will lead to an increase in the number of carbon emissions in the long run. This evidence is consistent with the studies of (Jayanthakumaran et al 2012;Wu et al 2015;Mahalik et al 2018). From a policy point of view, the study suggests that generating a sustainable healthy environment from the future fear of climate change and global warming should reduce excessive energy consumption without hampering rising growth.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 91%
“…Based on the balanced data and the spatial panel regression model of 31 provinces in China from 1996 to 2015, Liu et al [19] found that there is an inverted U-shaped relationship between income distribution and environmental quality, which indicates an appropriate level of income inequality helps to improve environmental quality. Studies have also shown that income inequality has different effects on the pollutant emissions from different countries [20]. Liu et al [21] used panel ARDL and quantile regression models to analyze the impact of income inequality on carbon emissions in the US.…”
Section: Literature Reviewmentioning
confidence: 99%